Activation and regulation of Toll-Like Receptors (TLRs) by helminth parasites - Venugopal, Priyanka Goel (2009)
Helminth (worm) infections are major public health problems that have important socioeconomic consequences for the more than 2 billion infected individuals. Chronicity (their hallmark) can lead to anemia (in hookworm infection), river blindness (onchcerciasis), cirrhosis (schistosomiasis), and elephantiasis (lymphatic filariasis). Although there have been many studies examining innate immune responses (including TLR expression and function) in response to intracellular pathogens, fewer have examined the interaction of the multicellular helminth parasites and the innate immune system. This review will focus on two “systemic” helminth parasitic infections (lymphatic filariasis and schistosomiasis) and the regulation of TLRs that may contribute to infection outcome.